Reconstruction of Digital Defects with the Free Proximal Ulnar Artery Perforator Flap. Issue 1 (27th January 2022) - Troisi, Luigi; Zanchetta, Francesco; Berner, Juan Enrique; Mosillo, Giuseppe; Pajardi, Giorgio Eugenio
Abstract : Background: The aim of post-traumatic digital reconstruction is to restore form and function, allowing early rehabilitation. In the absence of feasible local options, free tissue transfer can be a versatile and reliable alternative. The aim of this study was to describe our experience with the use of the free proximal ulnar artery perforator flap (PUPF). Methods: Our prospectively maintained free flap database was inquired for patients that had undergone digital reconstructions with free PUPFs. Results: Six patients that underwent digital reconstruction were eligible. The ipsilateral forearm was donor site of choice, with all flaps based on a perforator of the ulnar artery, without the need to compromise the main vessel. A superficial vein was routinely included with the flap. No flap failures were encountered. Mean hospital stay was 5.5 days, and all patients achieved a satisfactory functional result. Conclusions: The proximal ulnar perforator free flap offers an alternative for finger reconstruction, having the advantage of including thin and hairless skin from the proximal ulnar forearm. The vascular anatomy of the ulnar perforators seems to be constant. Furthermore, donor site morbidity is low, as the ulnar artery is not harvested with the flap, the donor site defect can generally be closed directly, and the scar is well concealed.